2015
DOI: 10.1016/j.actatropica.2014.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic polymorphism of Chrysomya albiceps (Wiedemann) (Diptera: Calliphoridae) may lead to species misidentification

Abstract: Species identification is an essential step in the progress and completion of work in several areas of biological knowledge, but it is not a simple process. Due to the close phylogenetic relationship of certain species, morphological characters are not always sufficiently distinguishable. As a result, it is necessary to combine several methods of analysis that contribute to a distinct categorization of taxa. This study aimed to raise diagnostic characters, both morphological and molecular, for the correct iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 72 publications
(129 reference statements)
1
11
0
Order By: Relevance
“…Even though morphological characters are widely used for species identification, some of the phenotypic traits that are easiest to be recognized visually often fail to delimit species accurately (Arribas et al, 2012;Lecocq et al, 2015). For example, several studies on insects, including flies (Grella et al, 2015), butterflies (Garzón-Orduña et al, 2018), and bees (Carolan et al, 2012;Ferrari & Melo, 2014;Huang et al, 2015) have shown that traits like color can be hard to interpret as diagnostic characters for species identification. Color traits may exhibit high rates of polymorphism due to environmental influences or genetic differences at a single single or multiple loci (Miyanaga et al, 1999;Uy et al, 2009;White & Kemp, 2016;Hines et al, 2017).…”
mentioning
confidence: 99%
“…Even though morphological characters are widely used for species identification, some of the phenotypic traits that are easiest to be recognized visually often fail to delimit species accurately (Arribas et al, 2012;Lecocq et al, 2015). For example, several studies on insects, including flies (Grella et al, 2015), butterflies (Garzón-Orduña et al, 2018), and bees (Carolan et al, 2012;Ferrari & Melo, 2014;Huang et al, 2015) have shown that traits like color can be hard to interpret as diagnostic characters for species identification. Color traits may exhibit high rates of polymorphism due to environmental influences or genetic differences at a single single or multiple loci (Miyanaga et al, 1999;Uy et al, 2009;White & Kemp, 2016;Hines et al, 2017).…”
mentioning
confidence: 99%
“…The material examined was identified on the basis of specific keys for each subfamily of Calliphoridae, i.e. Mariluis and Peris (1984) and Whitworth (2012) for Calliphorinae; Mariluis and Peris (1984), Mariluis et al (1994b), Rognes (1994) and Whitworth (2010, 2014) for Luciliinae; Dear (1985), González-Mora et al (1998), Mariluis et al (1994a), Rognes and Paterson (2005), Whitworth (2010) and Grella et al (2015) for Chrysomyinae, and Dear (1979) for Toxotarsinae. In the case of Mesembrinellidae the keys of Guimarães (1977), Bonatto and Marinoni (2005) and Wolff et al (2014) were used.…”
Section: Methodsmentioning
confidence: 99%
“…In Colombia, C. rufifacies was also the most abundant species on human cadavers (Barreto et al, 2002), reinforcing its superior competitive potential. Geographic expansion of C. rufifacies towards South America may lead to its widespread establishment, and molecular techniques have been used to determine if it has reached other countries within the continent (Grella et al, 2015). The ecological consequences of this dispersion can only be predicted using the results of quantitative studies.…”
Section: Effect Of Larval Competition On Adult Parametersmentioning
confidence: 99%